(untitled) (Journal of Open Law, Technology & Society, 2012)
The International Free and Open Source Software Law Book is a collaborative effort to create a coherent publication on legal aspects of FOSS in various jurisdiction. Marcus O’Leary kinldy accepted to have his review republished on IFOSS L. Rev